Epidemiology of the lymphatic-dwelling filarioid nematode Rumenfilaria andersoni in free-ranging moose (Alces alces) and other cervids of North America - Grunenwald, Caroline M.; Carstensen, Michelle; Hildebrand, Erik; Elam, Jacob; Laaksonen, Sauli; Oksanen, Antti; Gerhold, Richard W. (Parasites & Vectors, 2017)
Background: Moose (Alces alces) are a culturally and economically valued species in Minnesota, where the northeast population has decreased by 60 % since 2006. The cause of the decline is currently unclear; however, parasites, predation, and climate change have all been implicated. Nematode parasites are important pathogens in North American moose, potentially causing severe disease and mortality. Recent spread of Rumenfilaria andersoni, a filarioid nematode of moose, has been documented in Finnish cervids; however, little is known about the epidemiology of this parasite in North America. Methods: To investigate the prevalence and distribution of R. andersoni, 584 blood samples were collected from live-captured and dead animals and screened microscopically for the presence of microfilariae using a modified Knott's test. Microfilariae were identified based on morphological characteristics. A subset of Knott's-positive animals was subjected to polymerase chain reaction (PCR) with filarioid-specific primers targeting the first internal transcribed spacer region (ITS-1) of the rRNA gene cluster. Results: Rumenfilaria microfilariae were present in 20.5 % of Minnesota moose (n = 352), with slight fluctuations observed over four years. Minnesota white-tailed deer (Odocoileus virginianus) (n = 2) and moose (n = 44) from Alaska, Montana, Washington, Maine, and New Hampshire also harbored R. andersoni, suggesting this parasite occurs widely throughout North American moose herds, and white-tailed deer can serve as a patent host. Sequence analysis of cervid blood (moose, n = 15; white-tailed deer, n = 1) confirmed the identity of R. andersoni and revealed the existence of two distinct clades. Genetic comparisons of R. andersoni isolates from North America and semi-domesticated Finnish reindeer found the two groups to be closely related, supporting previous hypotheses that R. andersoni was recently introduced into Finland by the importation of deer from the United States. Conclusions: To the best of our knowledge these ...